Novel Radiofrequency Ablation Strategies for Terminating Atrial Fibrillation in the Left Atrium: A Simulation Study - Bayer, Jason D.; Roney, Caroline H.; Pashaei, Ali; Jaïs, Pierre; Vigmond, Edward J. (Frontiers in Physiology, 2016)
Pulmonary vein isolation (PVI) with radiofrequency ablation (RFA) is the cornerstone of atrial fibrillation (AF) therapy, but few strategies exist for when it fails. To guide RFA, phase singularity (PS) mapping locates reentrant electrical waves (rotors) that perpetuate AF. The goal of this study was to test existing and develop new RFA strategies for terminating rotors identified with PS mapping. It is unsafe to test experimental RFA strategies in patients, so they were evaluated in silico using a bilayer computer model of the human atria with persistent AF (pAF) electrical (ionic) and structural (fibrosis) remodeling. pAF was initiated by rapidly pacing the right (RSPV) and left (LSPV) superior pulmonary veins during sinus rhythm, and rotor dynamics quantified by PS analysis. Three RAF strategies were studied: i) PVI, roof, and mitral lines; ii) guided RFA with lines, circles, perforated circles, and crosses 0.5-1.5cm in length/diameter placed far and near rotor locations/pathways identified by PS mapping; and iii) sinus rhythm activation patterns streamlined with continuous RFA lesions (4-8) paralleling activation wavefronts. As in pAF patients, 2+/-1 rotors with cycle length 185+/-4 ms and short PS duration 452+/-401 ms perpetuated simulated pAF. Spatially, PS density had weak to moderate positive correlations with fibrosis density (RSPV: r=0.38, p=0.35, LSPV: r=0.77, p=0.02). PVI, mitral, and roof RFA failed to terminate pAF, but 1.5 cm RFA lines and perforated circles terminated meandering rotors from RSPV pacing when placed at regions with high PS density. Similarly, 1.5 cm RFA circles, perforated circles, and crosses terminated stationary rotors from LSPV pacing. The most effective strategy for terminating pAF was to streamline LA activation patterns with >4 RFA lines. Co-localizing 1.5 cm RFA lesions with LA regions of high PS density is a promising strategy for terminating pAF rotors. For patients immune to both PVI/roof/mitral and guided RFA strategies, streamlining patient-specific activation patterns is a robust but challenging alternative.